Fundamentos da extrusão termoplástica de pet food: uma revisão com base em literatura acadêmica - Franceschini, João Rafael Bortoti (Universidade Federal de São Carlos, 2025)
Pet food industry is experiencing significant growth in Brazil and worldwide, demanding efficient production processes and high-quality nutritional products. Thermoplastic extrusion is the main method of processing dry food for dogs and cats and the main operation in the production process. The objective of this study was to gather and analyze the fundamental technical aspects of pet food extrusion through a literature review supplemented by knowledge obtained during an internship at a dry pet food factory. The literature was compiled and analyzed to gather the main effects of raw materials and process parameters on processing conditions and extrudate quality. The analysis demonstrates that extrusion is not an isolated unit operation, but a system dependent on preceding steps, where particle size and mixture homogeneity directly influence process stability. Biochemical composition has significant impact on melt rheology: starch acts on the structure and expansion; proteins alter viscosity and mechanical energy demand; lipids act as lubricants; fibers modify the final texture and require more water. Controlling moisture content of the dough and efficiently applying thermal energy (steam) in the preconditioner are fundamental to optimizing cooking, reducing the mechanical energy demand in the extruder barrel. Physical configuration of the screw and its parameters determine shear rate and cooking. Die plate applies final mechanical energy as it controls expansion rate and kibble size and shape alongside with knife setup.
Fundamentals of thermoplastic extrusion of pet food: a review based on academic literature
Keywords: Extrusão; Ração; Alimentos secos para cães e gatos; Parâmetros de qualidade; Extrusion; Pet food; Dry dog and cat food; Quality parameters; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis